PROBLEM BASE LEARNING MENGGUNAKAN FLATFORM MOODLE BERBASIS MOBILE UNTUK MENINGKATKAN MODEL PEMBELAJARAN DI PENDIDIKAN TINGGI: Problem Base Learning (PBL);Mobile-Learning;Application Moodle. - Rini, Faiza; Rohayani, Hetty; Purnama, Fery; Anugrah, Septriyan; Pratama, Ade; -, Irsyadunas (JURNAL AKADEMIKA, 2021)
This study aims to improve and enhance the learning model in higher education by using a problem-based learning (PBL) model approach with a mobile-based Moodle platform. The data tested in this study consisted of 46 respondents, 20 lecturers and 26 students. The method used in this research is research and development in the Information Systems Audot Subject. The results showed that 80% of lecturers and 82.83% of students stated that this approach was practical to be used in the learning process. Therefore, this study can be a reference in the implementation of learning using the PBL approach with the Mobile-based Moodle platform at universities in Indonesia.